Review of Pixel-Level Image Fusion - 杨波 敬忠良 赵海涛 (Shanghai jiao tong da xue xue bao, 2010)
Image fusion can be performed at different levels： signal, pixel, feature and symbol levels. Almost all image fusion algorithms developed to date fall into pixel level. This paper provides an overview of the most widely used pixel-level image fusion algorithms and some comments about their relative strengths and weaknesses. Particular emphasis is placed on multiscale-based methods. Some performance measures practicable for pixel-level image fusion are also discussed. At last, prospects of pixel-level image fusion are made.